Improving Student’s Science Proces Skill in Biology Through The Inquiry Learning Model in Grade XI MIA 9 (ICT) SMA Negeri 1 Karanganyar Academic Year 2014/2015 - Rahmasiwi, Amining; Santosa, Slamet; Sari, Dewi Puspita (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
The objective of this research is to improve the skill of student’s science process skill of class XI MIA 9 (ICT)  SMA Negeri 1 Karanganyar academic year 2014/2015 through the use of inquiry learning model. The research is considered as Classroom Action Research that performed within 3 cycles and consists of 4 phase namely planning, action, observation, and reflection. The subject of research was students of XI MIA 9 (ICT) SMA Negeri 1 Karanganyar academic year 2014/2015. Data were obtained by observation, test, interview, and documentation. The obtained data were analyzed using qualitative descriptive technique. Data validation used triangulation methods. The  result showed that the application of inquiry learning model could improve the student’s science process skill of XI MIA 9 (ICT) SMA Negeri 1 Karanganyar academic year 2014/2015. The data showed that the mean value of all aspects had been improved from 31.41% in pracycle up to 49.14% in first cycle, than improve up to 62.05% in second cycle, and ended up by 76.45% at the final cycle. The conclusion of this research is that implementation of inquiry learning model was increasing the students science process skill in XI MIA 9 (ICT) in  SMA Negeri 1 Karanganyar academic year 2014/2015.Keywords: inquiry learning model, science process skill.